Equivalent descriptions of a discrete-time fractional-order linear system and its stability domains - Ostalczyk, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
Two description forms of a linear fractional-order discrete system are considered. The first one is by a fractional-order difference equation, whereas the second by a fractional-order state-space equation. In relation to the two above-mentioned description forms, stability domains are evaluated. Several simulations of stable, marginally stable and unstable unit step responses of fractional-order systems due to different values of system parameters are presented.
Keywords: fractional calculus; linear discrete-time systems; stability domain